Bringing DRM interoperability to digital content rendering applications - Serrão, C.; Dias, M.; Delgado, J. (Advances in Computer, Information, and Systems Sciences, and Engineering, 2006)
Modern high-bandwidth and open networks are a good medium for digital content distribution. However, digital content distribution over open networks can raise an all set of different issues related to piracy and intellectual propriety infringements and circumventions. Therefore, in order to avoid and overcome such issues, a good content security mechanism must be placed online to control and manage how the content access is processed. There are some actual discussions and initiatives going on to provide such controlling mechanisms, but perhaps one of the most highlighted is Digital Rights Management (DRM). Nevertheless, current DRM solutions, although solving part of the problem, most of the times end up adding an additional problem – interoperability. This paper will provide a description of a method and a system that is currently developing a new approach to the DRM interoperability issue. The method, which is described on the paper is part of a DRM system implementation whose description will also be provided here, and is based on the introduction of a middleware layer between the content rendering applications and the rights and content suppliers.